PENGARUH SUMBER N TERHADAP DEGRADASI DELTAMETRIN DAN PRODUKSI IAA OLEH PSEUDOMONAS SP. PIV-8-2 - Supriyati, Dyah (Perhimpunan Biologi Indonesia, 2015)
Deltamethrin is an active ingredient of insecticides such as decis, and its common pollutant observe in agricultural soil. Microbes that able to degrade deltamethrine and produced IAA as plant growth promoting hormone is important to support organic agriculture. The aim of this study was to find deltamethrin degrading bacteria capable of producing IAA and to evaluate the effect of nitrogen on degradation rate of deltametrin and IAA production. Deltametrin degrading Bacteria was isolated from non-organic rice fields around Cibinong Science Center. Deltamethrin degradation ability was evaluated in NMS medium with the addition of a nitrogen source: yeast extract, urea and NPK. Analyses of 16S rDNA showed that deltamethrin degrading bacteria and producing IAA was identified as Pseudomonas sp. PIV-8-2. Nitrogen siginificantly affect the degradation deltametrin rate, but not on IAA production. Only on the addition of yeast extract and urea significanly affect to IAA production after 2 days incubation.Keywords: Deltamethrin Degradation, IAA, Pseudomonas sp. PIV-8-2, Farming.